Colonisation dynamic and diversity patterns of Holocene forest snail fauna across temperate Europe: The imprint of palaeoclimate changes. (15th July 2020) - Horsák, Michal; Limondin-Lozouet, Nicole; Granai, Salome; Dabkowski, Julie; Divíšek, Jan; Hájková, Petra
Abstract: The development of biotic communities since the last glaciation has been shaped by both dramatic climate changes and pathways of species colonisation from glacial refugia. Although the growing body of literature has emerged recently on possible scenarios of postglacial colonisation, less is known about the effect of climate. We analysed the dynamics of Holocene mollusc succession with an undetected human impact using three well-dated sequences from spring tufa deposits across temperate Europe. For the first time, the detailed Holocene mollusc successions can be compared with climate parameters in the corresponding time windows. High-resolution palaeoclimate data accompanied the species data, and the data derived from stable isotope analyses. The number of closed-canopy forest species that colonised the sites until 5000 cal BP and the maximum number of species per sample systematically increased towards the interior of the continent. We also observed earlier colonisation of forest snail species in the Western Carpathians. While the aridity index was the best predictor of local species richness in Normandy and Luxembourg, minimum January temperature drove the variation in snail data in Slovakia. The short period of an abrupt cooling and drying around 8500 cal BP was found to stop the colonisation, sharply reducing the number of local species across the continent. Our results document the importance of climate for the colonisation and development of forest biota during the first half of the Holocene, both at continental and local scales. They also elucidate processes shaping the current distribution of forest snail fauna across the European temperate zone. Highlights: Holocene forest mollusc succession across temperate Europe is related to data from stable isotopes and palaeoclimatic models. Three well-dated tufa sequences from Normandy, Luxembourg and Slovakia provided high-resolution mollusc data. Abrupt cooling around 8500 cal BP temporarily stopped the colonisation and reduced the number of species across all sites. Aridity controlled local species richness in Normandy and Luxembourg, while minimum January temperature in Slovakia. Holocene climate constituted modern distribution of European forest snail diversity, sharply decreasing from east to west.